Modeling the drivers of trip satisfaction among Texas coastal anglers using creel survey data - Caren Collins; Shambhu Paudel; Elizabeth Harris; Hanna Bauer; Rileigh Hawk; Mark Fisher; Joel Anderson (PLoS ONE, 2026)
Angler satisfaction can be a complicated concept to explore, because angler perceptions are driven by a wide range of factors that interact in complex ways. Additionally, methods that quantify angler satisfaction often use after-the-fact mail surveys that can be impacted by latent effects such as long recall bias, which can systematically influence angler reporting. Here, we applied boosted regression tree modeling to assess angler satisfaction from creel intercept data collected at boat ramps on the Texas coast from 1991–2023. Anglers returning from fishing were asked to rate their trip on a scale of 0–10, and trip grades were parsed based on anglers targeting three popular sportfish (Spotted Seatrout, Red Drum, and Red Snapper). Angler satisfaction was modeled using observed catch data, weather on the day of trips, and other trip characteristics. Catch characteristics (total catch, angler catch-per-effort, catch length) were the most important predictors of angler satisfaction. There was also temporal and spatial variation in angler satisfaction, with trip grades increasing through time and from north to south. The relative importance of variables driving trip grade were different among angler groups, with weather-related factors (temperature, wind) being slightly more important for offshore Red Snapper anglers. A case study of Red Snapper anglers suggested that increasingly conservative federal and state regulatory measures through the time series appeared to have limited direct effects on angler satisfaction after accounting for temporal trends. Trip-level catch was the main predictor of reported angler trip grades, but spatial and temporal variation in trip grades suggest that angler satisfaction may be local and episodic. Variation in trip grades and the drivers of angler satisfaction among anglers targeting different species underscore the importance of a fisheries-level study design when assessing angler perceptions. These findings shed light on the influences of angler perceptions in Texas coastal fisheries and provide important insights for implementing future regulatory strategies.